Design and Harmonic Elimination of sinusoidal pulse width modulation (SPWM) Based Five Level Cascaded H-Bridge Multilevel Inverter for Photovoltaic System for Educational Purposes - Ganthia, Bibhu Prasad; Praveen, B. M. (Universitas Pendidikan Indonesia (UPI), 2023)
In this modern era, the electrical power system faces a shortage of fossil fuel-based energy sources. To overcome this problem, people more focus on giving towards renewable energy sources like solar energy, wind energy, and nuclear energy sources. This also can be used to overcome global warming and reduce pollution by fossil fuels. This study used a photovoltaic (PV) array to give supply to the Multilevel Inverter (MLI) with different irradiance values, which can be used for educational purposes. The sinusoidal pulse width modulation (SPWM) method is used here to control the converter. SPWM technique is the easiest technique than the other types of pulse width modulation (PWM) technique. In this technique the switching loss is very low, therefore efficiency is high. After the simulation, the output waveforms are similar to the sinusoidal waveform for the resistive load. In this topology, after simulation, the total harmonic distortion (THD) contents were found to be less by using an LC filter. The model is simulated in MATLAB/Simulink. The analysis of output voltage waveforms is discussed with the reduced THD.